An anti-aging corrosion-resistant electrically insulating repair coating and a method of making the same
Patent Information
- Application Number
- CN202611233766.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-20
AI Technical Summary
环氧树脂涂层附着力强、绝缘性能优良,但抗紫外老化性能差,长期户外使用易粉化开裂;氟碳涂层耐候性优异,但成本高且与金属基材附着力不足;有机硅涂层耐候性和疏水性好,但机械强度较低
本发明通过聚硅氮烷原位水解缩合形成致密二氧化硅层,协同抗氧剂捕获自由基,显著延缓环氧树脂的光氧与热氧老化,结合纳米氮化硼二维片层的迷宫效应,高效阻隔水、氧及氯离子渗透,同时介孔二氧化硅微胶囊在腐蚀介质触发下释放苯并三氮唑与磷酸锌,于金属表面生成不溶性络合/钝化膜,实现腐蚀损伤原位修复;环氧-聚硅氮烷复合体系不产生导电通路,纳米氮化硼的宽带隙与高击穿场强可强制电树枝分叉或终止,显著提升介电强度;本发明制得的涂层应用于海洋大气、工业污染环境中的电力设备中可有效降低腐蚀速率,显著延长设备维护周期。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating preparation technology, and relates to an anti-aging, corrosion-resistant, electrically insulating repair coating and its preparation method. Background Technology
[0002] With the upgrading of power system voltage levels and the widespread application of new energy equipment in harsh environments such as coastal areas, high humidity, and heavy pollution, the performance requirements for external insulation materials of electrical equipment are increasing. Insulating coatings not only need to have long-term stable electrical insulation performance, but also need to withstand the combined effects of various environmental factors such as ultraviolet aging, damp heat, salt spray, and chemical corrosion.
[0003] Currently, commonly used electrical insulating coatings mainly include epoxy resin coatings, polyurethane coatings, fluorocarbon coatings, and silicone coatings. Epoxy resin coatings have strong adhesion and excellent insulation properties, but poor resistance to ultraviolet aging and are prone to powdering and cracking after long-term outdoor use; fluorocarbon coatings have excellent weather resistance, but are expensive and have insufficient adhesion to metal substrates; silicone coatings have good weather resistance and hydrophobicity, but have low mechanical strength. To balance multiple properties, researchers have tried resin blending or multilayer composites, but once microcracks or electrical treeing damage occur in the coating, the insulation performance will irreversibly decline and is difficult to repair on-site. Summary of the Invention
[0004] The purpose of this invention is to provide an anti-aging, corrosion-resistant, electrically insulating repair coating and its preparation method, which has excellent anti-aging, corrosion resistance, and high insulation properties.
[0005] The objective of this invention can be achieved through the following technical solutions: An anti-aging, corrosion-resistant, and electrically insulating repair coating, the formulation of which is as follows (by weight): 30-50 parts epoxy resin, 10-20 parts polysilazane resin, 5-10 parts silica microcapsules, 3-5 parts modified nano boron nitride, 100-150 parts solvent, 0.5-2 parts leveling agent, 0.2-1 part defoamer, 1-2 parts antioxidant, and 5-15 parts curing agent. The silica microcapsules have a core-shell structure, with the core material comprising benzotriazole and zinc phosphate, and the wall material being mesoporous silica.
[0006] As a preferred embodiment of the present invention, the method for preparing the silica microcapsules is as follows: S2-1: Mix benzotriazole with zinc phosphate and dissolve it in an organic solvent to obtain solution A. Add solution A to water containing 0.5~1wt% Tween-80 and emulsify to obtain emulsion B. S2-2: Tetraethyl orthosilicate and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer are added to the emulsion B. The pH is adjusted to 8.5-9.5 using ammonia water, and the mixture is stirred for 4-12 hours at a temperature of 40-80°C. The silica microcapsules are obtained by centrifugation, washing, and vacuum drying.
[0007] As a preferred embodiment of the present invention, the curing agent is one or more of modified amine curing agents, polyamide curing agents, or latent imidazole curing agents.
[0008] As a preferred embodiment of the present invention, the modified boron nanonitride is boron nanonitride with a surface modified by a silane coupling agent, wherein the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.
[0009] As a preferred embodiment of the present invention, the solvent is one or both of ethyl acetate and butyl acetate.
[0010] As a preferred embodiment of the present invention, the defoamer is benzoin; the leveling agent is one or more of leveling agent F-400, leveling agent F-401, and leveling agent DH-4036; and the antioxidant is one or more of antioxidant 168, antioxidant 1010, and antioxidant 1017.
[0011] As a preferred embodiment of the present invention, benzotriazole and zinc phosphate are mixed in S2-1 at a mass ratio of 1:(0.5~1).
[0012] As a preferred embodiment of the present invention, the mass ratio of the total mass of benzotriazole and zinc phosphate to the mass of tetraethyl orthosilicate in S2-2 is 1:(2~4).
[0013] As a preferred embodiment of the present invention, the mass ratio of tetraethyl orthosilicate to polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer in S2-2 is 1:(0.1~0.3).
[0014] A method for preparing an anti-aging, corrosion-resistant, and electrically insulating repair coating, the specific steps of which are as follows: Epoxy resin and polysilazane resin are added to a solvent and stirred at 650-750 rpm for 10-30 minutes. Modified nano boron nitride is added and ultrasonically dispersed for 10-30 minutes at an ultrasonic power of 300-500 W. Then, silica microcapsules, leveling agent, and defoamer are added sequentially and stirred at 450-550 rpm for 10-30 minutes. Finally, a curing agent is added and stirred for 5-10 minutes to obtain the anti-aging, corrosion-resistant, and electrically insulating repair coating.
[0015] After curing, polysilazane forms a silica-like structure with excellent UV shielding capabilities, significantly delaying the photolytic cracking of epoxy resin. Simultaneously, the high thermal decomposition temperature of the silica structure inhibits the free radical chain reaction of epoxy molecules under long-term thermo-oxidative aging conditions. The introduction of antioxidants can capture free radicals generated during aging, terminating the chain oxidation reaction, thus forming a dual anti-aging mechanism of physical shielding and chemical inhibition with polysilazane.
[0016] The silica-like layer formed by the conversion of polysilazane possesses high density and low surface energy, effectively blocking the penetration of water molecules, oxygen, and chloride ions. Nano-boron nitride, with its two-dimensional sheet structure, is stacked in parallel orientation within the coating, creating a labyrinth effect that further extends the diffusion path of corrosive media, thus further reducing the permeability coefficient. Silica microcapsules, using mesoporous silica as the wall material, encapsulate a composite corrosion inhibitor of benzotriazole and zinc phosphate. When the corrosive media penetrates to the coating / metal interface, the microcapsules rupture, releasing the corrosion inhibitor. The released benzotriazole complexes with metal ions to form an insoluble chelate film, while the zinc phosphate is converted on the metal surface into iron phosphate or zinc phosphate complexes, collectively forming a dense passivation layer that prevents corrosion propagation.
[0017] After curing, epoxy resin forms a highly cross-linked three-dimensional network. The silica generated from the conversion of polysilazane is a wide-bandgap insulator; the composite of the two does not produce conductive pathways or interfacial polarization losses. The two-dimensional sheet structure of nano-boron nitride exhibits disordered orientation within the coating. When electrical trees sprout and extend from the electrode tip, the boron nitride sheets can force the trees to change direction, branch, or terminate, effectively extending the breakdown path length. Simultaneously, the high thermal conductivity of boron nitride can rapidly diffuse hotspots generated by partial discharge, suppressing thermally induced breakdown.
[0018] When the coating is exposed to the metal substrate due to mechanical scratches or the penetration of corrosive media, the silica microcapsules, stimulated by a decrease in local pH or an increase in ionic strength, open or rupture the mesoporous structure of the wall material, releasing benzotriazole and zinc phosphate from the core material in a controlled manner. Benzotriazole preferentially adsorbs onto the active sites on the metal surface, forming a dense chemisorption film that inhibits anodic dissolution. Zinc phosphate reacts with corrosion products to form insoluble phosphate precipitates, sealing microporous defects. This active repair mechanism can form a protective film in situ at the scratch site, significantly reducing the corrosion rate.
[0019] The beneficial effects of this invention are: This invention utilizes the in-situ hydrolysis and condensation of polysilazane to form a dense silica layer, which, in conjunction with antioxidants, captures free radicals and significantly delays the photo-oxidative and thermo-oxidative aging of epoxy resin. Combined with the labyrinth effect of nano-boron nitride two-dimensional sheets, it effectively blocks the penetration of water, oxygen, and chloride ions. Simultaneously, the mesoporous silica microcapsules release benzotriazole and zinc phosphate under the triggering of corrosive media, forming an insoluble complex / passivation film on the metal surface, achieving in-situ repair of corrosion damage. The epoxy-polysilazane composite system does not generate conductive pathways, and the wide bandgap and high breakdown field strength of nano-boron nitride can force the branching or termination of electrical trees, significantly improving dielectric strength. The coating prepared by this invention can effectively reduce the corrosion rate and significantly extend the equipment maintenance cycle when applied to power equipment in marine atmospheres and industrial polluted environments. Detailed Implementation
[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0021] It should be noted that, unless otherwise specified, the present invention does not specifically limit the source of the raw materials used in the following embodiments. Commercially available products or products prepared by conventional preparation methods that are well known to those skilled in the art can be used. Experimental methods that do not specify specific conditions are all conventional methods and conventional conditions well known in the art.
[0022] Example 1
[0023] An anti-aging, corrosion-resistant, and electrically insulating repair coating, the formulation of which is as follows (by weight): 40 parts epoxy resin (E-51), 15 parts polysilazane resin (number average molecular weight 1500), 7.5 parts silica microcapsules, 4 parts γ-aminopropyltriethoxysilane modified nano boron nitride, 125 parts solvent, 1.2 parts leveling agent F-400, 0.5 parts benzoin, 1.5 parts antioxidant 1010, 10 parts modified amine curing agent 593, and the solvent is a mixture of ethyl acetate and butyl acetate in a volume ratio of 1:1. The method for preparing the silica microcapsules is as follows: S2-1: Mix benzotriazole and zinc phosphate at a mass ratio of 1:0.7 and dissolve them in an organic solvent to obtain solution A. Add solution A to water containing 0.7wt% Tween-80 and emulsify to obtain emulsion B with a particle size of 1~5μm. S2-2: Tetraethyl orthosilicate and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer are added to emulsion B. The mass ratio of benzotriazole and zinc phosphate to tetraethyl orthosilicate is 1:3, and the mass ratio of tetraethyl orthosilicate to polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is 1:0.2. The pH is adjusted to 9 using ammonia water, and the mixture is stirred for 8 hours at 60°C. The silica microcapsules are obtained by centrifugation, washing, and vacuum drying.
[0024] A method for preparing an anti-aging, corrosion-resistant, and electrically insulating repair coating, the specific steps of which are as follows: Epoxy resin and polysilazane resin were added to a solvent and stirred at 700 rpm for 20 min. Modified nano boron nitride was added and ultrasonically dispersed for 20 min at an ultrasonic power of 400 W. Then, silica microcapsules, leveling agent, and defoamer were added in sequence and stirred at 500 rpm for 20 min. Finally, curing agent was added and stirred for 7 min to obtain the anti-aging, corrosion-resistant, and electrically insulating repair coating.
[0025] Example 2
[0026] The only difference between this embodiment and Example 1 is that the formulation of the repair coating is as follows, calculated by weight: 30 parts epoxy resin (E-51), 10 parts polysilazane resin (number average molecular weight 1500), 5 parts silica microcapsules, 3 parts γ-aminopropyltriethoxysilane modified nano boron nitride, 100 parts solvent, 0.5 parts leveling agent F-400, 0.2 parts benzoin, 1 part antioxidant 1010, 5 parts modified amine curing agent 593, and the solvent is a mixture of ethyl acetate and butyl acetate in a volume ratio of 1:1; the rest are the same as in Example 1.
[0027] Example 3
[0028] The only difference between this embodiment and Example 1 is that the formulation of the repair coating is as follows, calculated by weight: 50 parts epoxy resin (E-51), 20 parts polysilazane resin (number average molecular weight 1500), 10 parts silica microcapsules, 5 parts γ-aminopropyltriethoxysilane modified nano boron nitride, 150 parts solvent, 2 parts leveling agent F-400, 1 part benzoin, 2 parts antioxidant 1010, 15 parts modified amine curing agent 593, and the solvent is a mixture of ethyl acetate and butyl acetate in a volume ratio of 1:1; the rest are the same as in Example 1.
[0029] Example 4
[0030] The only difference between this embodiment and Embodiment 1 is that the preparation method of the silica microcapsules is as follows: S2-1: Mix benzotriazole and zinc phosphate at a mass ratio of 1:0.5 and dissolve them in an organic solvent to obtain solution A. Add solution A to water containing 0.5wt% Tween-80 and emulsify to obtain emulsion B with a particle size of 1~5μm. S2-2: Tetraethyl orthosilicate and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were added to emulsion B. The mass ratio of benzotriazole and zinc phosphate to tetraethyl orthosilicate was 1:2, and the mass ratio of tetraethyl orthosilicate to polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was 1:0.1. The pH was adjusted to 8.5 using ammonia water, and the mixture was stirred for 4 h at 40°C. The silica microcapsules were obtained by centrifugation, washing, and vacuum drying. The rest of the process was the same as in Example 1.
[0031] Example 5
[0032] The only difference between this embodiment and Embodiment 1 is that the preparation method of the silica microcapsules is as follows: S2-1: Mix benzotriazole and zinc phosphate at a mass ratio of 1:1 and dissolve them in an organic solvent to obtain solution A. Add solution A to water containing 1 wt% Tween-80 and emulsify to obtain emulsion B with a particle size of 1~5 μm. S2-2: Tetraethyl orthosilicate and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were added to emulsion B. The mass ratio of benzotriazole and zinc phosphate to tetraethyl orthosilicate was 1:4, and the mass ratio of tetraethyl orthosilicate to polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was 1:0.3. The pH was adjusted to 9.5 using ammonia water, and the mixture was stirred for 12 hours at 80°C. The silica microcapsules were obtained by centrifugation, washing, and vacuum drying. The rest of the process was the same as in Example 1.
[0033] Example 6
[0034] The only difference between this embodiment and Embodiment 1 is that the specific steps of the preparation method are as follows: Epoxy resin and polysilazane resin were added to a solvent and stirred at 650 rpm for 10 min. Modified nano boron nitride was added and ultrasonically dispersed for 10 min at an ultrasonic power of 300 W. Then, silica microcapsules, leveling agent, and defoamer were added in sequence and stirred at 450 rpm for 10 min. Finally, curing agent was added and stirred for 5 min to obtain the anti-aging, corrosion-resistant, and electrically insulating repair coating. The rest was the same as in Example 1.
[0035] Example 7
[0036] The only difference between this embodiment and Embodiment 1 is that the specific steps of the preparation method are as follows: Epoxy resin and polysilazane resin were added to a solvent and stirred at 750 rpm for 30 min. Modified nano boron nitride was added and ultrasonically dispersed for 30 min at an ultrasonic power of 500 W. Then, silica microcapsules, leveling agent, and defoamer were added in sequence and stirred at 550 rpm for 30 min. Finally, curing agent was added and stirred for 10 min to obtain the anti-aging, corrosion-resistant, and electrically insulating repair coating. The rest was the same as in Example 1.
[0037] Comparative Example 1 The only difference between this comparative example and Example 1 is that benzotriazole is not added in the preparation of the silica microcapsules; otherwise, they are the same as in Example 1.
[0038] Comparative Example 2 The only difference between this comparative example and Example 1 is that zinc phosphate is not added in the preparation of the silica microcapsules; otherwise, they are the same as in Example 1.
[0039] Comparative Example 3 The only difference between this comparative example and Example 1 is that silica, benzotriazole and zinc phosphate are physically mixed to replace silica microcapsules; otherwise, they are the same as in Example 1.
[0040] Comparative Example 4 The only difference between this comparative example and Example 1 is that polysilazane resin is not added; otherwise, they are the same as in Example 1.
[0041] Comparative Example 5 The only difference between this comparative example and Example 1 is that the nano-boron nitride is not modified with a silane coupling agent; otherwise, they are the same as in Example 1.
[0042] Performance testing Anti-aging performance test: QUV accelerated aging test machine was used, the light source was UVA-340 lamp tube, cycle: 60℃ ultraviolet light irradiation for 4h, 50℃ condensation for 4h, the test time was 2000h, gloss was measured before and after aging using a gloss meter, and the gloss retention rate was calculated.
[0043] Corrosion resistance test: A 5wt% NaCl neutral salt spray chamber was used at a temperature of 35±2℃. Continuous spraying was performed, and the time from the start of the test to the first blistering or rusting on the coating surface was recorded.
[0044] Electrical insulation performance test: The volume resistivity of the coating was tested at 200V using a high resistance meter in accordance with GB / T 1410-2006 standard. The specific experimental results are summarized in the table below.
[0045]
[0046] As can be seen from the above embodiments and comparative data, the coating prepared by the present invention has excellent anti-aging properties, corrosion resistance and high insulation properties.
[0047] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention are still within the scope of the present invention.
Claims
1. An anti-aging, corrosion-resistant, electrically insulating repair coating, characterized in that, The formulation of the repair coating is as follows (by weight): 30-50 parts epoxy resin, 10-20 parts polysilazane resin, 5-10 parts silica microcapsules, 3-5 parts modified nano boron nitride, 100-150 parts solvent, 0.5-2 parts leveling agent, 0.2-1 part defoamer, 1-2 parts antioxidant, and 5-15 parts curing agent. The silica microcapsules have a core-shell structure, with the core material comprising benzotriazole and zinc phosphate, and the wall material being mesoporous silica.
2. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 1, characterized in that, The method for preparing the silica microcapsules is as follows: S2-1: Mix benzotriazole with zinc phosphate and dissolve it in an organic solvent to obtain solution A. Add solution A to water containing 0.5~1wt% Tween-80 and emulsify to obtain emulsion B. S2-2: Tetraethyl orthosilicate and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer are added to the emulsion B. The pH is adjusted to 8.5-9.5 using ammonia water, and the mixture is stirred for 4-12 hours at a temperature of 40-80°C. The silica microcapsules are obtained by centrifugation, washing, and vacuum drying.
3. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 1, characterized in that, The curing agent is one or more of the following: modified amine curing agent, polyamide curing agent, or latent imidazole curing agent.
4. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 1, characterized in that, The modified boron nitride nanoparticles are boron nitride nanoparticles modified with a silane coupling agent, wherein the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.
5. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 1, characterized in that, The antioxidant is one or more of antioxidant 168, antioxidant 1010, and antioxidant 1017.
6. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 1, characterized in that, The defoamer is benzoin; the leveling agent is one or more of leveling agent F-400, leveling agent F-401, and leveling agent DH-4036; the solvent is one or two of ethyl acetate and butyl acetate.
7. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 2, characterized in that, In S2-1, benzotriazole and zinc phosphate are mixed at a mass ratio of 1:(0.5~1).
8. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 2, characterized in that, In S2-2, the total mass ratio of benzotriazole and zinc phosphate to tetraethyl orthosilicate is 1:(2~4).
9. The anti-aging, corrosion-resistant, and electrically insulating repair coating according to claim 2, characterized in that, In S2-2, the mass ratio of tetraethyl orthosilicate to poly(ethylene oxide-poly(propylene oxide-poly(ethylene oxide)) triblock copolymer is 1:(0.1~0.3).
10. A method for preparing an anti-aging, corrosion-resistant, electrically insulating repair coating as described in any one of claims 1 to 9, characterized in that, The specific steps of the preparation method are as follows: Epoxy resin and polysilazane resin are added to a solvent and stirred at 650-750 rpm for 10-30 minutes. Modified nano boron nitride is added and ultrasonically dispersed for 10-30 minutes at an ultrasonic power of 300-500 W. Then, silica microcapsules, leveling agent, and defoamer are added sequentially and stirred at 450-550 rpm for 10-30 minutes. Finally, a curing agent is added and stirred for 5-10 minutes to obtain the anti-aging, corrosion-resistant, and electrically insulating repair coating.